2009
DOI: 10.1002/aic.11921
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary approach to modeling gas hydrate/ice deposition from dissolved water in a liquid condensate system

Abstract: in Wiley InterScience (www.interscience.wiley.com).Gas hydrate/ice deposition from a dissolved water phase in a liquid condensate system was modeled using a mass and energy balance. The same modeling parameters were used to model three flow loop experiments (1.89 and 2.83 L/min flow rate deposition tests and a 1.89 L/min dissociation test) with acceptable accuracy. Relative changes in both temperature and pressure drop were modeled using an ice deposit with a 67% void fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…67 They proposed a hydrate wall-growth model in the same period. 68 Following up research efforts on hydrate deposition in various flow systems, 131–135 the first hydrate-deposition mechanism was not proposed until 2014, and was first put forth by Grasso et al 130 There are two suggested potential mechanisms of hydrate deposition in a multiphase flow based on experimental observations: hydrate deposition is either caused by hydrate film growth from a water layer on pipe walls or caused by hydrate particles accumulated on a hydrate base layer due to the cohesive forces between the particles. Hydrate deposition that is initiated directly from the closest gas layer on surfaces is possible in theory; however, this has not yet been observed.…”
Section: Anti-hydrate Deposition Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…67 They proposed a hydrate wall-growth model in the same period. 68 Following up research efforts on hydrate deposition in various flow systems, 131–135 the first hydrate-deposition mechanism was not proposed until 2014, and was first put forth by Grasso et al 130 There are two suggested potential mechanisms of hydrate deposition in a multiphase flow based on experimental observations: hydrate deposition is either caused by hydrate film growth from a water layer on pipe walls or caused by hydrate particles accumulated on a hydrate base layer due to the cohesive forces between the particles. Hydrate deposition that is initiated directly from the closest gas layer on surfaces is possible in theory; however, this has not yet been observed.…”
Section: Anti-hydrate Deposition Surfacesmentioning
confidence: 99%
“…In practice, the pipeline wall is the coldest component in the transport systems and provides intensive nucleation, deposition and adhesion sites for hydrate formation. 67,68 As such, pipeline walls can significantly affect surface-based hydrate nucleation, growth and agglomeration. The physical/chemical states and properties of pipeline walls can also coordinate hydrate deposition, and determine the interfacial interaction and adhesion between deposited hydrates and wall surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Three additional rules of thumb for hydrate formation from a condensate were determined by measurements in a liquid/condensate flow loop (Nicholas et al 2009), in conjunction with several laboratory measurements of adhesive forces between condensate hydrates and pipe materials.…”
Section: Fig 2-absolute-temperature Errors In Common Prediction Simumentioning
confidence: 99%
“…A numerical model for hydrate formation in wet-gas pipelines was formulated by Shagapov et al [13], which included the effect of methanol injection. Nicholas et al [14] carried out flowloop experiments and modelling of hydrate and ice deposition in a water-saturated condensate phase, while Rao et al [15] studied hydrate deposition from a water-saturated gas flowing over the surface of a cold tube. In each of these studies, the systems considered could be approximated as consisting of a fluid single-phase, with hydrate formation being limited by water availability.…”
Section: Introductionmentioning
confidence: 99%